Review of seafloor spreading around Australia. I. synthesis of the patterns of spreading - Veevers, J. J.; Powell, C. Mca; Roots, S. R. (Australian Journal of Earth Sciences, 1991)
The existing data on Late Mesozoic and Cenozoic seafloor spreading isochrons (reviewed in the companion paper by Veevers & Li) and fracture zone trends provide the basis for 12 reconstructions of the seafloor around Australia that spread during the dispersal of Argo Land, India, Antarctica, Lord Howe Rise/New Zealand and the Papuan Peninsula. The major changes of plate geometry in the Jurassic, Early Cretaceous, mid-Cretaceous, early Paleocene and early Eocene reflect global events. The pattern of spreading around Australia was determined by two long-standing (earlier Phanerozoic) factors that operated in a counter-clockwise direction: (I) penetration from the northwest by the Tethyan divergent ridge: and (2) rotation from the northeast of the Pacific convergent arc and back-arc. The only new feature of the modern pattern is the deep penetration by the Indian Ocean ridge into eastern Gondwanaland to fragment it intocontinents in contrast with the pattern up to 160 Ma ago of breaking off micro-continents.